(untitled) - Herbert, Jean (New York, 1967)
This book will help you to appreciate the significance of Japan’s own religion in everyday life, to recognize the key traditions and festivals (matsuri ) of the Shinto year, to understand what you will see at Shinto shrines and in Shinto rituals, to gain insights into the controversies surrounding Shinto, politics and nationalism.
Keywords: Shinto